The Effect of Classical Music Therapy on The Cognitive Function of The Elderly - Manopo, Monica Jetmin; Memah, Herlina; Warouw, Herman; Keintjem, Femmy; Alow, Getruida Banon Hermina (Jurnal Ilmiah Perawat Manado (Juiperdo), 2023)
Background: The elderly, better known as the "Elderly", are part of family members and community members who increase every year in line with the increase in life expectancy. If the health of the elderly is not handled properly, it will cause a decrease in physical and physiological functions resulting in more severe body damage, causing many complications and accelerating death. The purpose of the study was to determine the effect of music therapy on cognitive function of the elderly. This research method uses literature review research, namely a study in the form of a literature review of the results of previous research either textbooks or research journals. To obtain data in accordance with the specified topic, researchers conducted a search for national and international journals through two databases, namely, Science Direct and Google Schoolar. With the publication year 2015-2019 and researchers obtained 7 journals used for literature review. The results of the study based on 5 journals used, show that classical music therapy affects the cognitive function of the elderly. Conclusion: there is an effect of classical music therapy on cognitive function of the elderly.